Dual mechanisms for the regulation of brain-derived neurotrophic factor by valproic acid in neural progenitor cells - Ko, Hyun Myung; Jin, Yeonsun; Park, Hyun Ho; Lee, Jong Hyuk; Jung, Seung Hyo; Choi, So Young; Lee, Sung Hoon; Shin, Chan Young (The Korean journal of physiology & pharmacology, 2018)
Autism spectrum disorders (ASDs) are neurodevelopmental disorders that share behavioral features, the results of numerous studies have suggested that the underlying causes of ASDs are multifactorial. Behavioral and/or neurobiological analyses of ASDs have been performed extensively using a valid model of prenatal exposure to valproic acid (VPA). Abnormal synapse formation resulting from altered neurite outgrowth in neural progenitor cells (NPCs) during embryonic brain development has been observed in both the VPA model and ASD subjects. Although several mechanisms have been suggested, the actual mechanism underlying enhanced neurite outgrowth remains unclear. In this study, we found that VPA enhanced the expression of brain-derived neurotrophic factor (BDNF), particularly mature BDNF (mBDNF), through dual mechanisms. VPA increased the mRNA and protein expression of BDNF by suppressing the nuclear expression of methyl-CpG-binding protein 2 (MeCP2), which is a transcriptional repressor of BDNF. In addition, VPA promoted the expression and activity of the tissue plasminogen activator (tPA), which induces BDNF maturation through proteolytic cleavage. Trichostatin A and sodium butyrate also enhanced tPA activity, but tPA activity was not induced by valpromide, which is a VPA analog that does not induce histone acetylation, indicating that histone acetylation activity was required for tPA regulation. VPA-mediated regulation of BDNF, MeCP2, and tPA was not observed in astrocytes or neurons. Therefore, these results suggested that VPA-induced mBDNF upregulation was associated with the dysregulation of MeCP2 and tPA in developing cortical NPCs.